Command, control and communication (C3) during the COVID-19 pandemic; adapting a military framework to crisis response in a tertiary UK critical care centre. (May 2022) - Hutchings, SD; Perry, J; Mills, A; Bartley, F; Bartley, M; Park, CL
The COVID-19 pandemic of 2020 imposed significant strain on critical care services worldwide. The South London region experienced the largest numbers of critical care admissions in the United Kingdom with King's College Hospital one of the busiest centres. This article outlines, using a descriptive narrative, the significant changes that occurred within King's Critical Care as a result of the pandemic and the decisions that were taken to provide effective co-ordination and control to the expanded service, in part drawing on the military experience of two of the authors. The wider context of crisis and major incident leadership and management is also discussed contrasting different approaches used in civilian and military settings.